Development of illustrated comic-based learning media for islamic history for 8th grade students at muhammadiyah boarding school - Alfi Radhia Lilla; Salamah Sa'diatul Wafa; Anip Dwi Saputro; M Zainal arif; Afiful Ikhwan (At Turots: Jurnal Pendidikan Islam, 2024)
The development of comic-based educational tools for teaching Islamic history seeks to boost students' engagement and comprehension of the subject. This endeavor employs a research and development (R&D) approach, utilizing the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation phases. The development process begins with a needs analysis involving surveys and interviews with teachers and students. The design phase includes the creation of storyboards and comic scripts, which are then developed into comic media with the help of professional illustrators. Implementation was carried out in several junior high schools (SMP) to test the effectiveness of this media in learning. The research results show that the use of illustrated comics as a learning medium for Islamic history can increase student interest by 85% and material understanding by 90%. Students find illustrated comics more engaging and easier to understand compared to conventional textbooks. Evaluation was conducted through written tests and observations during the learning process, as well as interviews with teachers and students to obtain feedback. Based on the evaluation results, this illustrated comic media is effective in improving the quality of Islamic history learning. The conclusion of this study is that illustrated comic media can be an effective and attractive alternative in Islamic history learning, thus it is recommended for wider application in schools.